The global burden of gout: estimates from the Global Burden of Disease 2010 study. Issue 8 (3rd March 2014) - Smith, Emma; Hoy, Damian; Cross, Marita; Merriman, Tony R; Vos, Theo; Buchbinder, Rachelle; Woolf, Anthony; March, Lyn
Abstract : Objective: Gout is the most common cause of inflammatory arthritis in men, but has not previously been included in Global Burden of Disease (GBD) studies. As part of the GBD 2010 Study, the Musculoskeletal Disorders and Risk Factors Expert Group estimated the global burden of gout. Methods: The American Rheumatism Association 1977 case definition of primary gout was used in the study. A series of systematic reviews were conducted to gather the age-specific and sex-specific epidemiological data for gout prevalence, incidence, mortality risk and duration. Two main disabling sequelae of gout were identified; acute episode gout and chronic polyarticular gout, and used in the surveys to collect data to derive disability weights. The epidemiological data together with disability weights were then used to calculate years of life lived with disability (YLDs) for gout, for 1990 and 2010. No evidence of cause-specific mortality associated with gout was found. Gout disability-adjusted life years (DALYs), therefore, have the same value as YLDs. Results: Global prevalence of gout was 0.08% (95% uncertainty interval (UI) 0.07 to 0.08). DALYs increased from 76 000 (95% UI 48 to 112) in 1990 to 114 000 (95% UI 72 to 167) in 2010. Out of all 291 conditions studied in the GBD 2010 Study, gout ranked 138th in terms of disability as measured by YLDs, and 173rd in terms of overall burden (DALYs). Conclusions: The burden of gout is rising. With increasing ageing populations globally, this evidence is a significant prompt to optimise treatment and management of gout at individual, community and national levels.